FAST Ultra-Deep Survey (FUDS): The Star Formation Histories of FUDS0 Galaxies - Hongwei Xi; Lister Staveley-Smith; Bo Peng; Bi-Qing For; Bin Liu; Dejian Ding (The Astrophysical Journal Supplement Series)
We present the ultraviolet, optical, and infrared counterparts of 128 galaxies detected in neutral hydrogen (H i ) in the FAST Ultra-Deep Survey (FUDS) field 0 (FUDS0). H i mass upper limits are also calculated for 134 non-detections in the field. Stellar masses ( M _* ), star formation rates (SFRs), and star formation histories are computed by fitting spectral energy distributions using P ro S pect . The results show that H i -selected galaxies prefer recent long-lasting, but mild star formation activity, while H i non-detections have earlier and more intense star formation activity. Based on their distribution on the SFR versus M _* diagram, the typical evolution of H i -selected galaxies follows three distinct stages: (i) early stage: the total SFR increases, though the specific SFR decreases from 10 ^−8 to 10 ^−9 yr ^−1 ; (ii) mass accumulation stage: the SFR is steady, and stellar mass increase linearly with time; (iii) quenching stage: star formation activity quenches on a rapid timescale and at constant stellar mass. 37 non-detections are located on the star-forming main sequence, but are not detected in H i due to low sensitivity close to the field edges or close to strong radio frequency interference. Comparisons with the existing optical, optically selected H i , and H i catalogs show a good agreement with respect to measured M _* and SFR, with minor discrepancies due to selection effects. The ongoing full FUDS survey will help us better explore the evolutionary stages of H i galaxies through a larger sample.